2017
DOI: 10.1093/aje/kwx173
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Prevalence, Epidemiologic Characteristics, and Clinical Characteristics of Monoinfection and Coinfection in Diarrheal Diseases in Children in Tanzania

Abstract: The role of interactions between intestinal pathogens in diarrheal disease is uncertain. From August 2010 to July 2011, we collected stool samples from 723 children admitted with diarrhea (cases) to 3 major hospitals in Dar es Salaam, Tanzania, and from 564 nondiarrheic children (controls). We analyzed the samples for 17 pathogens and assessed interactions between coinfections in additive and multiplicative models. At least one pathogen was detected in 86.9% of the cases and 62.8%, of the controls. Prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 54 publications
(73 reference statements)
5
24
1
Order By: Relevance
“…However, among all the infants with Campylobacter infection (both symptomatic and asymptomatic), approximately 16% are infected solely with Campylobacter, and 84% showed comorbidities with other diarrheal pathogens (viruses, other bacteria, and parasites), including 67% of infants diagnosed with Campylobacter-related diarrhea. Many studies have reported that coinfection with multiple intestinal pathogens is common in infants in LMICs, and one proteobacterial infection (such as Escherichia coli, Salmonella, and Campylobacter) increases the host's susceptibility to other Proteobacteria (i.e., the proteobacterial bloom), so this should be kept in mind when considering the correlations observed in this study (1,49,50). Overall, our results indicate that approaches to control the risk of infection by other intestinal pathogens, such as sanitization, water treatment, and vaccination, are important to reduce diarrheal diseases in low-resource settings, but microbial gut compositions may also play a role.…”
Section: Discussionmentioning
confidence: 85%
“…However, among all the infants with Campylobacter infection (both symptomatic and asymptomatic), approximately 16% are infected solely with Campylobacter, and 84% showed comorbidities with other diarrheal pathogens (viruses, other bacteria, and parasites), including 67% of infants diagnosed with Campylobacter-related diarrhea. Many studies have reported that coinfection with multiple intestinal pathogens is common in infants in LMICs, and one proteobacterial infection (such as Escherichia coli, Salmonella, and Campylobacter) increases the host's susceptibility to other Proteobacteria (i.e., the proteobacterial bloom), so this should be kept in mind when considering the correlations observed in this study (1,49,50). Overall, our results indicate that approaches to control the risk of infection by other intestinal pathogens, such as sanitization, water treatment, and vaccination, are important to reduce diarrheal diseases in low-resource settings, but microbial gut compositions may also play a role.…”
Section: Discussionmentioning
confidence: 85%
“…The highest percentage of coinfections were detected in studies from Burkina Faso (65.5%, [27]), India (77%, [60]), and Tunisia (74.2%, [88]). Two recent studies on coinfections in diarrhoeal disease based on symptomatic and asymptomatic study populations from Rwanda and Zanzibar [109] and Tanzania [31] detected 65% and 58.1% of coinfections in symptomatic cases. Andersson and coworkers [109] found a negative association (coinfections less common than expected from probability) between rotavirus and norovirus GII in symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an increase in studies from low-resource settings [20,21,22,23,24,25,26,27,28], reflecting a growing awareness of the importance of noroviruses as enteropathogens. Studies on the burden of norovirus are complicated by the frequent occurrence of asymptomatic infections [29], a significant proportion of norovirus disease that manifests with vomiting only symptoms [30], and a high prevalence of coinfections with other gastroenteritis pathogens [31].…”
Section: Introductionmentioning
confidence: 99%
“…were identified in the studied population only as concomitant pathogens. Co-infections among enteric pathogens have been frequently described [ 36 38 ]. However, still there is a controversy regarding the clinical impact of concomitant infections on the diarrheal illness.…”
Section: Discussionmentioning
confidence: 99%